Observations on the behaviour and damage of Bradysia paupera Tuomikoski (Diptera Sciaridae) in glasshouses (Bollettino di zoologia agraria e bachicoltura, 2024)
Infestations caused by Diptera were recorded in several glasshouses of the Veneto region (North-Eastern Italy), utilized for the propagation of horticultural and ornamental plants. Economic damage was recorded on artichoke (obtained by micro-propagation), petunia and poinsettia. Diptera occurring in a glasshouse center were monitored in order to study the species composition, population dynamics and insect-plant relationships. The most common species belonged to three families, in particular Sciaridae (Bradysia paupera Tuomikoski), Ephydridae (Scatella stagnalis Fallén) and Psychodidae. Only B. paupera was a pest for cultivated plants. Samplings, made on artichoke, begonia, snowbread and petunia, showed the dominance of sciarids over the remaining groups and their continuous increase during the cultivation period. Monitoring Diptera at ground level revealed the dominance of Psychodidae but B. paupera persisted at low population levels under the cultivation zone. The pest caused a damping-off of artichoke seedlings, leaf chewing and damping-off of petunia seedlings. Yellow sticky traps were used in order to obtain data on Diptera composition and B. paupera's seasonal abundance. A relation between the number of adults, or of larvae, and misses was found on artichoke. B. paupera infestations on petunia caused a significant misses increase. Apparently, the pest did not cause damage on begonia and snowbread. Insecticide treatments carried out against adults were ineffective suggesting alternative pest control strategies.
Keywords: Bradysia paupera; Sciaridae; glasshouse; monitoring; damage